When they go low, we go high: Scholars of color, activism, and educational research in a post-truth era - Childs, Joshua; Johnson, Sarah (Education Policy Analysis Archives, 2018)
In the post-truth era, research from scholars of color will serve greater utility due to their propensity to speak truth to power, counter inaccurate narratives about marginalized populations, and challenge the politics that emerge during the post-truth era. This paper will highlight how scholars of color have centered race and social justice within their research, and provide examples of how the educational research community should counter the current post-truth era. We propose that scholars of color should be more prominent in our research agendas. This includes citing more of their work, supporting research agendas that positions ‘race’ at the center, and promoting critical scholarship that moves away from deficit language. If we are going to speak truth to power in today’s post-truth climate, then educational researchers must produce critical scholarship that challenges the lies and myths that permeate in a post-truth era.